Chemical Resistivity of Rubberized Concrete with Steel Tire Wire - Loganathan, Kamalesh Reddy (Universiti Teknologi PETRONAS, 2020)
The idea of producing rubberized concrete was initiated due to the increase in waste tires with the development of the automobile industry as well as the inefficiency of the degrading capabilities of the tires in natural conditions. This indirectly led to an increase in the global warming and subsequently producing environmental challenges. Thus, the appearance of the rubberized concrete provides an effective method to dispose tires as the scrap tires is recycled into crumb rubber and used as a replacement of aggregates in concrete. This on the other hand grew to a larger scale when it was known to be implemented in the construction industry. It is now highly used in road engineering, bridges and railway tracks. Rubberized concrete is the mixing of crumb rubber into concrete and the properties of the rubberized concrete varies depending on the percentage of crumb rubber in addition to it.